Third Five Year Plan Annual Plan 1964-65 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1964)
Agricultural Production and Land Development, Training Centres, Consolidation of Holdings, Minor Irrigation, Soil Conservation, Animal Husbandry, Dairying and Milk Supply , Forests, Fisheries, Warehousing and Marketing.
Planning Department, Government of Andhra Pradesh